Protein profile of some strains of Ranikhet disease virus* - KUMANAN, K; AHAMED, N MUSTAQ; VENKATESAN, R A (The Indian Journal of Animal Sciences, 2013)
Five field isolates of Ranikhet disease virus (RDV) were subjected to sodium dodecyl sulphate polyacrylamide-gel electrophoresis, both before and after adaptation to chicken embryo fibroblast culture and BHK-21 cells for studying their protein fractions. The pattem of protein fractions were identical and contained 8 fractions. Minor variations were observed In the clcctrophoretic mobilities of the isolates after adaptation to cell-culture systems.